DIANA ABU-JABER’S NOVEL "CRESCENT" AND ITS ARABIC TRANSLATION: CONTRASTIVE TEXT ANALYSIS - Sulaiman, Noor A. (European Scientific Journal, ESJ, 2015)
The main objective of this paper is to compare and contrast between two parallel texts. The Source Text (ST) is Diana Abu-Jaber’s novel "Crescent" (2003) and the Target Text (TT) is its Arabic rendition "Al-Hilal" translated by Fouad Srouji, a freelance translator and editor. Interlingual comparisons between the two equivalent texts were made at all language levels in order to examine whether there are any lexical, syntactic, semantic, morphological, or discourse problems/differences between the two versions of the novel. This paper also seeks to see whether the translator was sensitive to the linguistic, social, and cultural differences of both the source text language and the target text language. Upon completion of this paper, it was found the translator was loyal to a large extent to the ST at the different linguistic levels though this was sometimes done at the expense of the naturalness of the TT. The findings may be useful in further investigating loyalty to the Source Language (SL) in combination with naturalness in the target language (TL).